Forest Fire Risk Zone Mapping of Aalital Rural Municipality, Dadeldhura District, Nepal - Prajwol Babu Subedi; Keshav Ayer; Mahamad Sayab Miya; Bhawana Parajuli; Barsha Sharma (Journal of Multidisciplinary Applied Natural Science, 2022)
Forest fire is one of the leading causes of forest and wildlife loss. The objective of this study was to use satellite imagery and Geographic Information System techniques to assess the forest fire risk zonation map of the Aalital rural municipality. This rural municipality is a part of the Sudurpaschim province, Nepal; is prone to forest fires. Four fire risk zones were established in the study area i.e. very high, high, medium, and low-risk zone. Thematic layers were derived from topographic maps and satellite imageries. For the delineation of fire risk zones, a multi-parametric weighted index model i.e. the FRI (Fire Risk Index) method was adopted. The fire incidence data provided by MODIS were used to validate the resulting forest fire risk zone map. About 25.17% of the total study area lies under the very high-risk zone followed by 46.51% under high risk, 25.68% under medium risk, and 2.62% under the low-risk zone. It can be inferred that the majority of the area is at high risk of forest fire. This map of fire risk zone can help in disaster and forest management as valuable data to prepare effective measures for appropriate fire risk management in the area.